Mineralocorticoid Deficiency and Treatment in Congenital Adrenal Hyperplasia. (12th April 2010) - Padidela, Raja; Hindmarsh, Peter C.
Abstract : Approximately 75%–80% of patients with Congenital Adrenal Hyperplasia (CAH) fail to synthesize sufficient mineralocorticoids to maintain salt and water balance. In most instances genotype can predict mineralocorticoid deficiency in CAH. Early recognition and replacement with 9α -fludrocortisone and salt supplements will prevent development of potentially lethal salt losing crises. In infancy a relative state of aldosterone resistance exists and replacement dose of 9α -fludrocortisone based on body surface area is higher during infancy compared to childhood and adults. Salt supplementation is generally not required after weaning is started. Regular monitoring of blood pressure and measurements of plasma electrolytes and renin are required to prevent complications of under or over dosage.